1인용 전동휠체어의 안전 운행을 위한 지능형 통합 제어보드 기능 개선 연구 - 김진술(Jinsul Kim); 조영빈(Young-Bin Cho) (디지털콘텐츠학회논문지, 2018)
본 논문에서는 1인용 스마트 전동휠체어의 보다 안전한 주행을 위한 지능형 통합 제어보드의 기능 개선 솔루션을 제안한다. 기존 국내·외의 전동휠체어 제품의 경우 안전 관련 기능 또는 장치가 포함되지 않은 경우가 많기 때문에 노약자 및 장애인이 지속적으로 증가하는 추세를 보이는 현 상황에서 전동휠체어가 관련된 사고의 발생 빈도 또한 지속적인 증가추이를 보이고 있다. 하지만 현재 상용되는 제품들에는 중고가형 이상의 전동휠체어에만 기본적인 완충작용 장치가 설치되어 있는 한계로 저가형의 제품에도 안전관련 기능이 필요한 실정이다. 따라서, 스마트 제어 플랫폼의 개발을 통해 전동휠체어 이동 중 사용자가 감지하지 못하는 장애물 또는 지형변화를 자동으로 감지 및 전동휠체어의 모터를 자동으로 제어함으로써 사용자가 안정적인 주행을 할 수 있도록 다양한 전동휠체어에 적용 가능한 스마트 전동휠체어 통합제어보드를 제시한다. The purpose of this study was to propose a functional improvement solution of integrated control board for safe driving of Smart electric wheelchair for a single person. In the case of existing electric wheelchair products in Korea and elsewhere, safety-related functions or devices are not included in many cases. Therefore, the incidence of electric wheelchair-related accidents is continuously increasing in the current situation in which the elderly and the disabled people have been continuously increased. However, currently only high and middle-priced products are equipped with basic safety devices in electric wheelchairs, so low-priced products require safety related functions. Therefore, sensing obstacles that the user can not recognize while moving an electric wheelchair and detecting automatically the terrain change to control the motor by developing a smart control platform. This provides an integrated control board that can be applied to various electric wheelchairs for more stable driving. KCI Citation Count: 4